Covid-19 livelihood crisis, social cohesion challenges and mitigation options: an empirical study among low-income groups and migrant workers in Bangladesh - Mostafa, Sanaul; Islam, M. Shahidul; Akter, Nahida; Ahmed, Kawsher (Brac University, 2022)
Includes bibliographical references.